Analisis Kepuasan Layanan GoFood dengan Metode User Experience Questionnaire - Bayu Saputra; Nor Anisa (Universitas Methodist Indonesia, 2024)
Online food delivery services are increasingly popular, with GoFood being one of the most sought-after platforms, offering convenience for users in meeting their daily food needs. This study aims to analyze user satisfaction with GoFood services using the User Experience Questionnaire (UEQ) method. This method was chosen as it evaluates user experience across various aspects, including attractiveness, clarity, efficiency, and stimulation. Data were collected through questionnaires distributed to 150 active GoFood users. The findings reveal that clarity and efficiency scored the highest, reflecting ease of use and service speed.Nevertheless, the stimulation aspect, which pertains to innovation and the appeal of the service, still requires improvement. These results offer valuable insights for developers to refine the user experience and bolster competitiveness in an ever-evolving market.